An analysis of stakeholders’ perspectives regarding the factors that affect job satisfaction in HR Departments of Multinational Organizations in Greece through the economic crisis. - Karathymios, Christos (2017)
This research aims to understand the factors that affect employees’ job satisfaction in HR departments in multinational organizations in Greece. Demographic variables (age, gender, education, position in the organization, work experience) are taken into consideration so as to examine participant’s differences and mention possible differentiations in their job satisfaction level driven by these variables. Moreover, the research examines the impact of the economic crisis in participants’ job satisfaction. Finally, as the term “job satisfaction” is quite theoretical and its interpretation is based on each individual’s experiences participants were asked to describe how they perceive this term and, subsequently, explain the factors that affect it. In order to realize this research, interviews were conducted. The interviewees who took part in the process are professionals in HR departments in multinational organizations. The group was mixed (based on the demographic variables) so as a reliable and valid result to be achieved. Results indicated that participants are satisfied with their current job. Findings show that employees’ job satisfaction increased through the period of economic crisis. In addition, the factors that are designated by the participants as of what affects their job satisfaction are working environment, relations with the co-workers, recognition, advancement, pay, and the values, the culture and the administration of the company. Finally, differences based on the demographics were noticed.